2020
DOI: 10.3168/jds.2019-17303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding live yeast at 2 dosages on performance and feeding behavior of dairy cows under heat stress

Abstract: The objectives were to evaluate the effects of feeding different amounts of supplemental live yeast (LY) on performance and digestion of cows under heat stress. Sixty Holstein cows, 27 multiparous and 33 primiparous, were blocked by parity and milk yield in the first 20 d in milk (DIM) and randomly assigned to receive 0, 0.5, or 1.0 g/d of LY, resulting in daily intakes of 0, 14.2, and 37.6 billion cells, respectively, of Saccharomyces cerevisiae strain CNCM I-1077 from 30 to 107 DIM. Cows were milked twice da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 47 publications
5
16
0
2
Order By: Relevance
“…In dairy cows, LY supplementation has been shown to induce an increased meal frequency and a decreased meal size (11) , that may limit the increase in HP shortly after a meal (by decreasing the amount of nutrients and energy consumed at each meal). Moreover, in dairy cows submitted to heat stress, LY dietary supplementation induces changes in feeding behavior associated with improved lactation performance (12) . Another study furthermore evidenced a decrease in rectal temperature of 0.2 °C (13) in LY supplemented cows that may increase the temperature difference between the animal and its environment, thus helping them to face heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…In dairy cows, LY supplementation has been shown to induce an increased meal frequency and a decreased meal size (11) , that may limit the increase in HP shortly after a meal (by decreasing the amount of nutrients and energy consumed at each meal). Moreover, in dairy cows submitted to heat stress, LY dietary supplementation induces changes in feeding behavior associated with improved lactation performance (12) . Another study furthermore evidenced a decrease in rectal temperature of 0.2 °C (13) in LY supplemented cows that may increase the temperature difference between the animal and its environment, thus helping them to face heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Yeast culture supplementation has been observed to improve milk fat yield in early and mid-lactation dairy cows (Dias et al, 2018;Perdomo et al, 2020). Olagaray et al ( 2019) observed a 0.13-kg/d increase in milk fat yield at 4 and 5 wk postpartum, feeding 19 g/d of yeast culture during the peripartal period, which was similar to the 0.16-kg/d increase in milk fat yield observed in YC cows compared with control.…”
Section: Milk Production and Milk Componentsmentioning
confidence: 84%
“…Bruno et al (2009) report a rise in milk yield of 1.2 kg/day in dairy cows within first 130 days of lactation fed with the yeast additive. Perdomo et al (2020) recorded that milk yield tended (p = 0.10) to increase linearly, a 1.4 kg/day difference between 0 and 3.76 10 10 cfu/head/day treatments, with incremental feeding of live yeast. Desnoyers et al (2009) in a meta-analysis on S. cerevisiae supplementation to ruminants, estimated a mean milk yield response to yeast of +0.78 kg/day, for a 650-kg cow-equivalent.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, De Vries and Chevaux (2014) record an increasing trend in fat content -rise by 0.16%, and milk fat yield -rise by 0.07 kg/day, in cows which had yeast added to their ration by the dosage 1 • 10 10 cfu/head/day, however, no effect on milk protein content or milk fat content was noted in their study. Perdomo et al (2020) evaluated the effect of different doses of live yeast on the performance of dairy cows (0, 1.42 and 3.76 • 10 10 cfu/head/day). They found that protein tended (p = 0.08) to increase with increasing dose of live yeast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation